Tomato yellow leaf curl virus from Sardinia is a whitefly-transmitted monopartite geminivirus. - Kheyr-Pour, A (1991)
The genome of an isolate of tomato yellow leaf curl virus from Sardinia, Italy (TYLCV-S), a geminivirus transmitted by the whitefly Bemisia tabaci, has been cloned and sequenced. The single circular DNA molecule comprises 2770 nucleotides. Genome organisation closely resembles that of the DNA A component of the whitefly-transmitted geminiviruses with a bipartite genome. A 1.8 mer of the TYLCV-S genome in a binary vector of Agrobacterium tumefaciens is infectious upon agroinoculation of tomato plants. Typical tomato yellow leaf curl disease symptoms developed about three weeks after inoculation. The disease was transmitted by the natural vector B.tabaci from agroinfected plants to test plants, reproducing in this way the full biological cycle and proving that the genome of TYLCV-S consists of only one circular single-stranded DNA molecule. Contrary to the other whitefly-transmitted geminiviruses described so far, there is no evidence for the existence nor the necessity of a second component (B DNA) in the TYLCV-S genome.